Use of Fagopyrum esculentum and Ocimum basilicum to control laminar erosion, in Sorocaba-SP (Research, Society and Development, 2022)
The use of land when well elaborated, promotes the possibility of minimizing harmful processes such as water erosion and promotes the good use of natural soil fertility. Among the forms of planning aimed at soil conservation there are those that are based on soil coating, thus the objective of this work was to evaluate the use of crops such as Fagopyrum esculentum (Buckwheat) and Ocimum basilicum (Basilicum) in the control of laminar erosion. In this sense, 03 plots containing different forms of implantation and 01 plot with exposed soil all with approximately 3.0 m², for the analyses simulated rainfall with intensity of 20mm, performing at the end of each simulation the collection of water and soil from laminar erosion in buckets allocated at the end of the plots, in addition, the crop cover index was monitored over time. The result showed that soil and water loss is inversely proportional to the cover index (r = -0.99), “Trigo Mourisco” and “Manjericão” tend to cover the soil between 2 and 5 weeks, respectively. Thus, the use of plants that allow soil coating promotes over time better use of its physical-chemical characteristics, improving local productivity for agricultural uses.